The relationship between cultural intelligence and team effectiveness among administrative support staff at Setia Ecohill Sdn Bhd / Raja Firdaus Raja Aziz - Raja Aziz, Raja Firdaus (2017)
Organization nowadays builds to perform their function through teams and groups. There want to look for individual that have a good performance in a group and also have the skill to communicate and adapt with people from various cultures effectively. Therefore, people should know and familiar with other cultures and they need to interact with people from other cultures properly. For this purpose, they need cultural intelligence. The purpose of these studies is to examine the relationship between cultural intelligence and its four factors with team effectiveness in Setia Ecohill Sdn Bhd at Selangor. The sample consisted of 80 administrative support staff from Setia Ecohill Sdn Bhd. The participant received a questionnaire to measure the four factor model of cultural intelligence and team effectiveness. The reliability of the questionnaire also was tested by conducting a pilot study. They were analyse by using SPSS software version 23. The Pearson correlation coefficients were used to determine the relationship between cultural intelligence and each factors of it with team effectiveness. According to the results, the cultural intelligence (r=.612) and all of its factor, metacognitive (strategy) (r=.468), cognitive (knowledge) (r=.446), motivational (drive) (r=.604) and behavioural (action) (r=.613) showed a strong positive and significant relationship with team effectiveness. In the future, the organization can promote cultural intelligence by training the employees to make them familiar with the differences and similarities across cultures It is also recommended for the future researcher to conduct the study in another location or company. It is also much recommended for the future researcher to use mixed method in collecting data in order to provide more information on team effectiveness.